Sesquioxides of iron in moist temperate forests of the state of Hidalgo, Mexico - Acevedo Sandoval, Otilio Arturo; Cruz Chavez, Enrique; Cruz Sánchez, Misael; Prieto García, Francisco; Prieto Méndez, Judith (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
Total iron dissolved and iron forms extracted with acid ammonium oxalate, sodium pyrophosphate and dithionate- citrate- bicarbonate were studied in Alisol soils in the municipality of Acaxochitlán, State of Hidalgo, México. The studied soils present different kind of forests: Pinus patula schlecht and Cham (Pp), Pinus teocote, (Pt) and Quercus spp, (Q). The objective of this investigation is to determinate if the vegetation modifies the different fraction of iron (Fe) in the soil. The highest total iron content (14.5% of Fe2O3) was observed in the soils with Pp vegetation, the highest percent of ferrihydrite (38.0% of total Fe present in the soil) and of iron-organic matter complex and amorphous iron oxides (20.9% and 16.3% respectively of total Fe in the soil) were found in the Pt forest. Free iron forms (56.7% of total Fe in the soil) and crystalline iron forms (goethite/ hematite) were predominant in the soils with Pp forest. The most weathered soil was the one with Q vegetation, a higher evolution in the process of iron oxi-hydroxides structural organization was found in the soils with Pt and Pp. The type of forest vegetation influences the degree of soil evolution, and distribution, content and forms of Fe oxides in order of highest to lowest total Fe content in the soil was Pinus patula > Quercus spp > Pinus teocote.